Effect of some processing treatments on shelf life of camel milk in comparison to cow milk - KUMAR, ARUN; SETH, RAMAN; KUMAWAT, DINESH (The Indian Journal of Animal Sciences, 2021)
In the present study, cow and camel raw milk showed positive clot on boiling (COB) test after 6 h and 14 h respectively. Pasteurization enhanced the shelf life of cow milk twice without any substantial increase in the shelf life of camel milk. Both raw and pasteurized camel milk had better shelf life at ambient (25°C) as well as refrigerated (7°C) temperatures than that of cow milk. Development of acidity was much slower in camel milk as compared to cow milk. Further, camel milk was found to be less prone to lipolysis as compared to cow milk. FFA content in COB positive camel and cow milk was 0.7 meq/L for 14 h storage and 1.9 meq/lit for 6 h storage only. Camel and cow raw milk showed positive alcohol test at 6 h and 4 h of storage at ambient (25°C) temperature respectively. Pasteurization and refrigeration enhanced the shelf life of camel and cow milk.